Prosperity. Better business makes the greater good - Mayer, Colin (Oxford University Press, 2018)
What is business for? Day one of a business course will tell you: it is to maximise shareholder profit. This single idea pervades all our thinking and teaching about business around the world but it is fundamentally wrong, Colin Mayer argues. It has had disastrous and damaging consequences for our economies, environment, politics, and societies. In this urgent call for reform, 'Prosperity' challenges the fundamentals of business thinking. It sets out a comprehensive new agenda for establishing the corporation as a unique and powerful force for promoting economic and social well being in its fullest sense - for customers and communities, today and in the future. Mayer is a leading figure in the global discussion about the purpose and role of the corporation. He presents a radical and carefully considered prescription for corporations, their ownership, governance, finance, and regulation. Drawing together insights from business, law, economics, science, philosophy, and history, he shows how the corporation can realize its full potential to contribute to economic and social well being of the many, not just the few. 'Prosperity' tells us not only how to run successful businesses but also how policy can get us there and fix our broken system.